Story of blind baba Abdalla - Macaw (Macaw books, 2010)
Take children to a journey through the fabulous world of Arabian nights. Captivating text and wonderful illustrations make this series comes with an animated CD that contains the story in animation, and fun activities like color on screen, sketch pad, and animated games like ' match the scenes' 'spot differences and jigsaw puzzles' - an added incentive for owning these must-read books.
Location: 3B
Keywords: Fiction book